Controllability for mechanical systems with symmetries and constraints - Ostrowski, Jim P.; Burdick, Joel W. (Zielona Góra: Uniwersytet Zielonogórski)
This paper derives controllability tests for a large class of mechanical systems characterized by nonholonomic constraints and symmetries. Recent research in geometric mechanics has led to a single, simplified framework that describes this class of systems, which includes examples such as wheeled mobile robots; undulatory robotic and biological locomotion systems, such as paramecia, inchworms, and snakes; as well as the reorientation of satellites and underwater vehicles.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka